The Effect Of Team Quiz Method On Students’ Reading Comprehension Skill In Narrative Text At SMP Swasta Al-Hikmah - Shally Ari Adinda, Dahlia Sirait (LPPPI Publishing, 2022)
This study aims to determine the effect of the quiz team method on students' reading comprehension skill in narrative texts in the eighth grade of SMP Swasta Al-Hikmah. The method used in this study is a quantitative method. This research design is experimental research. It was carried out into two classes namely the experimental class (VIII-1) which consisted of 30 students was taught using the quiz team method while the control class (VIII-2) consisted of 30 students taught without the team quiz method. The instrument of this research is a multiple choice test consisting of 10 questions. The tests consist of two types, namely pre-test and post-test to collect data. After collecting data, the writer then analyzed the test results using the t-test formula. Based on the analysis of the data obtained, it shows that the t-test is 4.59 and the t-table is 1.67 for ? = 0.05. Because the t-test is higher than the t-table (4.59 > 1.67), this means that Ho is rejected and Ha is accepted. Based on the results, it was concluded that using the quiz team method was effective in improving students' reading comprehension skill in narrative text at eight grade of SMP Swasta Al-Hikmah